2009
DOI: 10.1104/pp.109.145854
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tobacco Aquaporin1 in Improving Water Use Efficiency, Hydraulic Conductivity, and Yield Production Under Salt Stress      

Abstract: Tobacco (Nicotiana tabacum; C3) plants increase their water use efficiency (WUE) under abiotic stress and are suggested to show characteristics of C4 photosynthesis in stems, petioles, and transmitting tract cells. The tobacco stress-induced Aquaporin1 (NtAQP1) functions as both water and CO 2 channel. In tobacco plants, overexpression of NtAQP1 increases leaf net photosynthesis (A N ), mesophyll CO 2 conductance, and stomatal conductance, whereas its silencing reduces root hydraulic conductivity (L p ). Never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
181
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(197 citation statements)
references
References 49 publications
13
181
0
3
Order By: Relevance
“…The aquaporin blocker mercury (HgCl 2 ) was shown to alter stomatal aperture in Vicia faba (Yang et al, 2006), but this effect has not been reproduced (Shope and Mott, 2006) and can be questioned because of mercury cellular toxicity. Finally, steady state changes in stomatal conductance have been reported in plants with genetically altered aquaporin functions (Hanba et al, 2004;Flexas et al, 2006;Cui et al, 2008;Sade et al, 2010). Yet, these changes could reflect a genuine function of aquaporins in stomata or altered water or CO 2 transport (Flexas et al, 2006) in other leaf tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The aquaporin blocker mercury (HgCl 2 ) was shown to alter stomatal aperture in Vicia faba (Yang et al, 2006), but this effect has not been reproduced (Shope and Mott, 2006) and can be questioned because of mercury cellular toxicity. Finally, steady state changes in stomatal conductance have been reported in plants with genetically altered aquaporin functions (Hanba et al, 2004;Flexas et al, 2006;Cui et al, 2008;Sade et al, 2010). Yet, these changes could reflect a genuine function of aquaporins in stomata or altered water or CO 2 transport (Flexas et al, 2006) in other leaf tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The specific role of TIP-AQPs was demonstrated by overexpressing another Solanaceae AQP that localizes to the plasma membrane and not the tonoplast. Overexpression of this AQP, Nicotiana tabacum AQP1 (NtAQP1), was previously reported to improve tomato plant abiotic stress tolerance (these mutant tomato plants were referred to as Tom-NtAQP; Sade et al, 2010). Here, these Tom-NtAQP1 plants did not show any resistance to TYLCV upon inoculation (Supplemental Fig.…”
Section: Tip-aqps Are Involved In Resistance To Tylcv In Tomato and Amentioning
confidence: 79%
“…Plant AQPs are involved in regulating both transpiration and hydraulic conductivity (Aharon et al, 2003;Boursiac et al, 2005;Postaire et al, 2010;Pou et al, 2013). Differential levels of AQP expression correlate with differences in the rate of leaf transpiration under normal and abiotic/ biotic stress conditions (Siefritz et al, 2002;Parent et al, 2009;Sade et al, 2010Sade et al, , 2012b.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis plants with a reduced expression of genes encoding aquaporins PIP1 and 2 after the withdrawal of drought showed a reduced transpiration and turgor recovering difficulties [33]. Under optimal conditions and salt stress, tobacco plants overexpressing the aquaporin gene NtAQP1 had increased water use and increased net photosynthesis [34]. It has been shown that gene expression of aquaporins in plants occurs in the early stages of seed germination [35].…”
Section: Discussionmentioning
confidence: 99%